Harmonisasi Jabatan Notaris Dan Informasi dan Transaksi Elektronik Dalam Cyber Notary - Kautsar, Mensalathiif; Salam, Abdul (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
In the industrial revolution 4.0, everything is becoming digital. Additionally, the COVID-19 pandemic, and the difficulty of meeting face to face at that time, pushed everything to be done electronically or online. This is no exception for notaries, who have difficulty adapting to this all-electronic era. This research is doctrinal research which uses materials, namely literature and statutory regulations. The research results show that the Information and Electronic Transactions Law has accommodated the existence of electronic documents and information, but the Law on Notary Positions cannot expressly recognize the existence of electronic documents to be included in authentic deeds. Where other countries have adapted this cyber notary, Indonesia has not been able to apply it due to obstacles in these regulations. The exceptions contained in the Information and Electronic Transactions Law can be removed to provide space for cyber notaries in Indonesia, but the Notary Position Law must also be adjusted to provide clear guidelines for the implementation of cyber notaries.